Значення педагогічної практики у процесі підготовки майбутнього вчителя початкової школи у Фінляндії - Котун, Кирил (Studies in Comparative Education, 2013)
У статті проаналізовано та обґрунтовано значення педагогічної практики у процесі підготовки майбутнього вчителя початкової школи у Фінляндії. Визначено основні етапи педагогічної практики та принципи її реалізації. Виділено предмет практики у змісті курикулуму педагогічної освіти. Окреслено значення розроблення власних портфоліо студентів та їх важливість протягом всього періоду педагогічної практики. Зазначено рекомендації щодо необхідних умінь у майбутніх учителів після проходження практичного навчання В статье проанализированы и обоснованы значение педагогической практики в процессе подготовки будущего учителя начальной школы в Финляндии. Определены основные этапы педагогической практики и принципы ее реализации. Выделено предмет практики в содержании курикулума педагогического образования. Очерчены значения разработки собственных порт фолио студентов и их важность в течение всего периода педагогической практики. Отмечено рекомендации необходимых умений у будущих учителей после прохождения практического обучения. In the article we consider the importance of pedagogical practice in primary teaching training in Finland. We note that practice teaching is organized in special practice schools as well as in regular schools. Many practice periods follow each other, and every period is integrated into the totality of the teacher education programme. At the start, the students observe pupils of different ages, their roles as group members, and their ways of interacting in the instruction process in different classes and grades. Every study period has its aims and characteristics. Practice usually consists of successive internships from the beginning to the advanced study levels. Although the organization of practice studies is predominantly the same in different universities, such studies may be applied and adapted to use according to local conditions. Following introductory practice at the beginning of studies, there is, first, basic practice, then field school practice, and, finally, teaching practice. The structure of teaching practice studies may vary considerably from university to university, up to fifteen credits on average. During basic practice, students become acquainted with the teaching of different subjects, the basic forms of teaching, and of the evaluation of teaching and learning. Students plan, teach, and evaluate lessons in different subjects. The basic practice is completed in the university training school, and the supervising class teachers are also responsible for portfolio work. A compiled portfolio may also contain teaching material that a given student may have produced along with his or her account of practice and his or her own work evaluation. On the whole, the portfolio concentrates on an analysis of the teaching of various subjects. Students also observe the teaching of their classmates and convey their assessments in their portfolios. The practice period includes much discussion about student teaching and the student portfolios. All practice studies are integrated with other studies, and basic practice teaching relates mainly to didactics and to courses in subject didactics. The field school practice teaching and the final practice teaching are study periods that may be combined when the students are widening their views regarding teaching as a profession and different ways of working as a teacher. The aim is for the students to seek their own ways of working as classroom teachers. They work together with their supervising teachers and with increasing responsibility in the same class, over a relatively long period. This practice internship is often combined with field trips to particular educational institutions. Students also become acquainted with the issues of special education. During these final practice periods, they are expected to employ research-based thinking skills and to identify possible themes for their respective theses if they do not continue their Proseminar work. The whole study project is linked to these practice studies. The main principle of the programme is the integration of the various aspects of the teacher education programme through research-based thinking and argumentation. However, this principle as such is not sufficient. How research is defined and what is meant by a research-based approach are also essential. An extensive and liberal interpretation of research is applied